(untitled) (Journal of Economic Research & Business Administration, 2021)
This paper aims to analyze the current state and development perspectives of the agricultural sector of the Central Asian countries. It shows that the sector, despite the decreasing trends in many indicators, plays an important role in terms of production, employment, and trade. The paper also considers trade indicators of the region with a focus on the pandemic period. It finds that the countries of Central Asia depend on agricultural imports. However, the Central Asian countries play an important role in the global agricultural market in terms of wheat and cotton production. The paper identifies major disadvantages and challenges for regional agriculture, including rising food prices, climate change, quality of institutions, and productivity. It provides recommendations for the regional policymakers, including escaping trade wars, export bans and other restrictions, and liberalization of trade in agricultural products. In terms of improving the competitiveness of the regional agriculture, the policymakers should focus on climate change adaptation strategies, stimulate capital investment, and improve institutional quality. These policies will require both individual and regional efforts of the governments, businesses, and universities of Central Asia. The findings and recommendations of the paper can be beneficial for policymakers and scholars of Central Asia. Key words: Central Asia, agriculture, trade, Kazakhstan.